1997
DOI: 10.1093/humrep/12.12.2773
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the zona pellucida carbohydrate distribution in human oocytes failing to fertilize in vitro

Abstract: The mammalian zona pellucida contains several glycoproteins whose oligosaccharide moieties are known to play a key role in the interaction with spermatozoa. Since zona pellucida defects may represent one of the most likely causes of failed fertilization in human in-vitro reproduction, we have studied the carbohydrate composition and distribution over the human zona pellucida by means of lectins. Donated, not inseminated cumulus-oocyte complexes, from cohorts with high fertilization rates, and fertilization-fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…We next labeled CGs in fixed eggs using fluorescent dye-conjugated Maclura pomifera agglutinin (MPA) (Becker and Hart, 1999;Dosch et al, 2004;Mei et al, 2009;Talevi et al, 1997). At 1 min post activation (mpa), CGE in WT and Mdchs1b eggs were comparable.…”
Section: Delayed Cge In Mdchs1b Mutantsmentioning
confidence: 99%
“…We next labeled CGs in fixed eggs using fluorescent dye-conjugated Maclura pomifera agglutinin (MPA) (Becker and Hart, 1999;Dosch et al, 2004;Mei et al, 2009;Talevi et al, 1997). At 1 min post activation (mpa), CGE in WT and Mdchs1b eggs were comparable.…”
Section: Delayed Cge In Mdchs1b Mutantsmentioning
confidence: 99%
“…Morphofunctional studies of human MII oocytes aged in culture show contradictory result: Ducibella et al [61] found an occurrence of CG exocytosis and consequent zona hardening, while Talevi et al [62] showed an intrinsic alteration in ZP with no alteration of CG distribution. Our results underline an abnormal reduction in amount (and inner density in some cases) of suboolemmal CG in all aged samples, when compared with those of fresh controls.…”
Section: Cortical Granulesmentioning
confidence: 99%
“…S1A-F in the supplementary material). Wheat germ agglutanin (WGA), used to identify cortical granules in human oocytes (Talevi et al, 1997), labeled 1 m vesicles in C. elegans oocytes and meiosis I embryos, but not in older embryos ( Fig. 1A-C).…”
Section: Identification Of Cortical Granulesmentioning
confidence: 99%